Cross‐linking reactions in food proteins and proteomic approaches for their detection. Issue 5 (12th July 2021) - Renzone, Giovanni; Arena, Simona; Scaloni, Andrea
Abstract: Various protein cross‐linking reactions leading to molecular polymerization and covalent aggregates have been described in processed foods. They are an undesired side effect of processes designed to reduce bacterial load, extend shelf life, and modify technological properties, as well as being an expected result of treatments designed to modify raw material texture and function. Although the formation of these products is known to affect the sensory and technological properties of foods, the corresponding cross‐linking reactions and resulting protein polymers have not yet undergone detailed molecular characterization. This is essential for describing how their generation can be related to food processing conditions and quality parameters. Due to the complex structure of cross‐linked species, bottom‐up proteomic procedures developed to characterize various amino acid modifications associated with food processing conditions currently offer a limited molecular description of bridged peptide structures. Recent progress in cross‐linking mass spectrometry for the topological characterization of protein complexes has facilitated the development of various proteomic methods and bioinformatic tools for unveiling bridged species, which can now also be used for the detailed molecular characterization of polymeric cross‐linked products in processed foods. We here examine their benefits and limitations in terms of evaluating cross‐linked food proteins and propose future scenarios for application in foodomics. They offer potential for understanding the protein cross‐linking formation mechanisms in processed foods, and how the inherent beneficial properties of treated foodstuffs can be preserved or enhanced.